THE ROLE OF THE BRIMOB MEMBERS OF THE POLRI IN IMPLEMENTING COMMUNICATION AFFAIRS TO SUPPORT THE OPERATIONAL DUTIES OF THE BRIMOB: Analisis Peranan Anggota Brimob Polri dalam Pelaksanaan Urusan Komunikasi untuk Mendukung Tugas Operasional Satbrimob - FH, Ilham Agung Nugroho; Nurwati; Hakim, Aal Lukmanul (DE'RECHTSSTAAT, 2024)
The communication media used by the Mobile Brigade Corps (Satbrimob) must be appropriate for operational purposes. There must be no misuse of communication devices, as communication facilities are still lacking.The purpose of this research is: To determine and analyze the accountability of Brimob members in the Mobile Brigade Corps (Satbrimob) Communications Division. To determine and analyze the obstacles faced by Brimob members assigned to the Communications Division within the Mobile Brigade Corps (Satbrimob). A research method is needed to gather research materials. The research method used is a normative juridical research method, where law is conceptualized as norms, rules, principles, or dogmas. Research findings: In carrying out police operations, Brimob acts as a backup unit for regional units, providing support, command, and control within the regional unit as the user. In police activities, Brimob personnel are directed towards routine activities in preparation and improving their capabilities in handling jihad, riots, search and rescue, and counter-terrorism. Meanwhile, police operations are carried out in the form of regional operational patterns, namely participating in police operations against forms of public order disturbances that disturb the community, especially local contingencies in the region and centralized regional operations, especially against threats on a national and international scale.